INVESTIGATING AND ANALYZING WOMEN’S SOCIOCULTURAL BARRIERS IN USING THE PUBLIC TRANSPORT SYSTEM IN AHVAZ METROPOLIS - Majid GOODARZI; Mohammad Ali FIROOZI; Omid SAEIDI (European Journal of Geography)
The present study aimed to investigate and analyze women’s sociocultural barriers in using public transport of Ahvaz Metropolis. This research is applied- theoretical in terms of purpose and descriptive-analytical in terms of method. The data were collected through library studies, surveys, and interviews with citizens and experts of public transport. The ARAS decision-making method was used to rank the barriers. For zoning the barriers in Ahvaz, the interpolation kriging model in ARCGIS 10.3 software was employed. The results show that the sociocultural barriers of each age group of women are different in each public transport mode. Ranking these barriers shows that sexism looks, men's sexual looks, relatives, families, disapproval, and the drivers’ nonsense talk, respectively, are the major barriers to bus and taxi use, walking, and cycling. In addition, zoning the barriers indicated that the further one moves from north to south of the city, the greater the barriers are. A regional view of this zoning confirms that about 90% of the area of districts 4 and 8 are in the high and very high range, and 30% of district 3 is in the high range. These districts are less favourable than other districts of Ahvaz, but zone 2 is the most favourable one, as it is entirely in low and very low ranges.